Using Acoustic Information to Perceive Room Size: Effects of Blindness, Room Reverberation Time, and Stimulus. (September 2013) - Kolarik, Andrew J; Pardhan, Shahina; Cirstea, Silvia; Moore, Brian C J
Blind participants greatly rely on sound for spatial information regarding the surrounding environment. It is not yet established whether lack of vision to calibrate audition in far space affects blind participants' internal spatial representation of acoustic room size. Furthermore, blind participants may rely more on farthest distance estimates to sound sources compared with sighted participants when perceiving room size. Here we show that judgments of apparent room size and sound distance are correlated, more so for blind than for sighted participants. Sighted participants judged a reverberant virtual room to be larger for speech than for music or noise stimuli, whereas blind participants did not. The results suggest that blindness affects the use of room reverberation for distance and room-size judgments.